Hepatic UDP-Glucuronosyltransferase Is Responsible for Eslicarbazepine Glucuronidation - Loureiro, Ana I.; Fernandes-Lopes, Carlos; Bonifácio, Maria J.; Wright, Lyndon C.; Soares-da-Silva, Patricio (Drug metabolism and disposition, 2011)
Eslicarbazepine acetate (ESL) is a once-daily novel antiepileptic drug approved in Europe for use as adjunctive therapy for refractory partial-onset seizures with or without secondary generalization. Metabolism of ESL consists primarily of hydrolysis to eslicarbazepine, which is then subject to glucuronidation followed by renal excretion. In this study, we have identified that human liver microsomes (HLM) enriched with uridine 5′-diphosphoglucuronic acid give origin to a single Escherichia coli β-glucuronidase-sensitive eslicarbazepine glucuronide (most likely the O-glucuronide). The kinetics of eslicarbazepine glucuronidation in HLM was investigated in the presence and absence of bovine serum albumin (BSA). The apparent Km were 412.2 ± 63.8 and 349.7 ± 74.3 μM in the presence and absence of BSA, respectively. Incubations with recombinant human UDP glucuronosyltransferases (UGTs) indicated that UGT1A4, UGT1A9, UGT2B4, UGT2B7, and UGT2B17 appear to be involved in eslicarbazepine conjugation. The UGT with the highest affinity for conjugation was UGT2B4 (Km = 157.0 ± 31.2 and 28.7 ± 10.1 μM, in the absence and presence of BSA, respectively). There was a significant correlation between eslicarbazepine glucuronidation and trifluoperazine glucuronidation, a typical UGT1A4 substrate; however, no correlation was found with typical substrates for UGT1A1 and UGT1A9. Diclofenac inhibited eslicarbazepine glucuronidation in HLM with an IC50 value of 17 μM. In conclusion, glucuronidation of eslicarbazepine results from the contribution of UGT1A4, UGT1A9, UGT2B4, UGT2B7, and UGT2B17, but the high-affinity component of the UGT2B4 isozyme may play a major role at therapeutic plasma concentrations of unbound eslicarbazepine.